2021
DOI: 10.3390/cells10081995
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Mitophagy-Related Pathways at the Crossroads of Genetic Pathways Involved in Familial Sarcoidosis and Host-Pathogen Interactions Induced by Coronaviruses

Abstract: Sarcoidosis is a multisystem disease characterized by the development and accumulation of granulomas, the hallmark of an inflammatory process induced by environmental and/or infectious and or genetic factors. This auto-inflammatory disease mainly affects the lungs, the gateway to environmental aggressions and viral infections. We have shown previously that genetic predisposition to sarcoidosis occurring in familial cases is related to a large spectrum of pathogenic variants with, however, a clustering around m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 142 publications
(185 reference statements)
0
12
0
Order By: Relevance
“… 3 Furthermore, two recently published studies have demonstrated, by evaluating the genes involved in the pathogenesis of sarcoidosis and the interactome of the SARS‐CoV‐2 host cell, that the two diseases may involve common cellular pathways in the regulation of autophagy and mitophagy, specifically TBK1 and BRD4. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 Furthermore, two recently published studies have demonstrated, by evaluating the genes involved in the pathogenesis of sarcoidosis and the interactome of the SARS‐CoV‐2 host cell, that the two diseases may involve common cellular pathways in the regulation of autophagy and mitophagy, specifically TBK1 and BRD4. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…3 Furthermore, two recently published studies have demonstrated, by evaluating the genes involved in the pathogenesis of sarcoidosis and the interactome of the SARS-CoV-2 host cell, that the two diseases may involve common cellular pathways in the regulation of autophagy and mitophagy, specifically TBK1 and BRD4. 4,5 Also noteworthy is the diagnostic interpretation of the cutaneous lesions at the time of SARS-CoV-2 infection. In this case, these lesions were initially attributed to the SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism is unclear, we postulate that ORF8 partly contributes to COVID-19 pathogenesis via this system. Moreover, some proteins in Class 1, including IL17RA, growth differentiation factor 15, FK506-binding protein 10, and PLAT, are associated with sarcoidosis pathogenesis ( 22 ). Indeed, it is known that ORF8 plays a role in COVID-19 pathogenesis, and a variant with its absence leads to milder illness ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Several studies have demonstrated that COVID‐19 might share common features with sarcoidosis involving common mechanistic cellular pathways around the regulation of autophagy and mitophagy. 11 , 12 …”
Section: Discussionmentioning
confidence: 99%